“Yo sé hablar, dije” The conditions for Peruvian domestic workers to speak out for their rights - Carola Mick (Les Cahiers ALHIM)
Based on the analysis of autobiographic stories told by Peruvian domestic workers in Lima, the present article discusses the conditions for these women to stand up and speak out for their rights. Studying the speakers' use of the two verba dicendi (“verbs of speaking”) decir and hablar, it reconstructs the communicative competence these marginalised actors themselves define as necessary for their active participation in society. The analysis allows for discussing the conditions for women in Latin America to participate in the struggle against social inequalities, as well as the role and responsibility of the ethnographic research process with regard to this competence.